Radiographic evaluation of experimentally induced nephrosis in goats - KUMAR, RAKESH; PANDEY, N N; SINGH, G R; SETIA, H C (The Indian Journal of Animal Sciences, 2013)
Intravenous pyelography (IVP) with pnecumoperitoneum (PP) was undertaken in normal and induceed nephrotic goats. In normal goats, the technique provided visualization of both the kidneys, renal pelvis, ureter and uTlnary bladder at 10 mm post-admilmtration of sodium iothalarnate (70%). In mercuric chloride- and oxytetracycline-induced nephrosis in goats, the urinary tract could not be visualized even 60 min post-adminstration of dye indicatlng severe failure of renal excretory function. However, in gentamicim-abused goats, renal excrelory function was not significanlly altered owing to a very mild renal damage. It was concluded that IVP with PP could he a dependable diagnostic test for varied degree of renal msufficiency in rominants.